PENETAPAN RHODAMIN B PADA SAMPEL LIPSTIK DENGAN MENGGUNAKAN KLT-SPEKTROFOTODENSITOMETRI - N.N.A.S. Devi; N.P.M.P.P. Winarni; I.P. Priyasana; G.A.D. Mayagita; V. Rahmadinha; K.M. Limba; A.A.I.K. Dewi; I K.N. Sanjaya; N.P.L. Laksmiani (Jurnal Kimia (Journal of Chemistry), 2020)
Lipsticks are widely used by women to beautify themselves. Among the various colors that make lipstick more interesting, red color lipstick is the most demanded one. Rhodamine B is a synthetic dye that banned for use and certified as a hazardous material according to Minister of Health of Indonesian Republic No. 376/Menkes/Per/1990 because it causes liver damage, kidney and lymph glands damage, followed with organ enlargement. The aim of this study is to identify Rhodamine B in lipsticks in the market. Samples were taken from 3 shops in Denpasar City and Badung Regency. Samples were soaked with amonia solution with using wool yarn to extract the rhodamine B dye and identification using TLC plate silica gel GF254 withn-butanol: ethyl acetate: amonia (1322:5.2:6.5) as mobile phase then detected with UV light 254 and 366 nm. Identification by spectrophotodensitometry where the TLC plate was observed in the TLC Analyzer to observe the AUC in each spot formed. The AUC obtained from the instrument illustrates the concentration of the analyte in each bottle. The result shows that 3 examined samples doesn’t contain rhodamine B. Keywords: Rhodamin B, Lipstik, TLC, Spectrophotodensitometry